Pengaruh citra merek dan kualitas produk terhadap loyalitas konsumen sepatu futsal - Filemon Redo; Donant Alananto Iskandar (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to determine whether there is an influence between brand image and product quality on consumer loyalty for Nike futsal shoes in East Jakarta. This research uses a quantitative approach through a survey of 88 users of Nike futsal shoes. The sampling method is non probability sampling. The results of the hypothesis (t test) indicate that the brand image variable is significantly related to consumer loyalty. This is indicated by t count 2.139 which is greater than t table and product quality variables are also significantly related to consumer loyalty with t count 2.082 which is greater than t table. The conclusion from this study that the brand image and product quality variables are related to consumer loyalty. This can be interpreted that, decrease or increase in customer loyalty depends on the brand image of the quality of products made and in accordance with the needs and desires of consumers